2017
DOI: 10.3233/ajw-170011
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Groundwater Extraction in the Coastal Aquifers of Purba Midnapur District of West Bengal in India under the Constraint of Saline Water Intrusion

Abstract: The objective of this paper is to assess the field-based study on the sub-surface characteristics and groundwater quality variation in the coastal region of Purba Midnapur district, West Bengal, India. The fact that the coastal area receives inadequate surface water, the use of groundwater has become increasingly important for domestic, irrigation and industrial purposes; however threat exists associated with groundwater over-exploitation that leads to the intrusion of seawater. Hydro-geochemical site characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To mitigate this problem, the state government has prohibited groundwater‐irrigated boro rice in some pockets, but the recent depletion and bore rice cultivation in large parts may lead to a high bio‐accumulation of arsenic. In contrast, salinity is a problem in the nearby coastal district of East Medinapur, West Bengal (Figure 7d) (Maity et al, 2017), which is likely to aggravate because of higher rates of groundwater depletion. In fact, the 2011 government policy has enabled millions of farmer the easy access to groundwater, even deemed to usher in a new green revolution (Mukherji et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this problem, the state government has prohibited groundwater‐irrigated boro rice in some pockets, but the recent depletion and bore rice cultivation in large parts may lead to a high bio‐accumulation of arsenic. In contrast, salinity is a problem in the nearby coastal district of East Medinapur, West Bengal (Figure 7d) (Maity et al, 2017), which is likely to aggravate because of higher rates of groundwater depletion. In fact, the 2011 government policy has enabled millions of farmer the easy access to groundwater, even deemed to usher in a new green revolution (Mukherji et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A modeling framework had been established that predicted the reservoir inflow taking the future climatic scenarios. Maity et al (18) observed that due to excessive over extraction of groundwater; seawater intrusion was conducted in Purba Medinipur, India. On the experimental studies, they found high values of groundwater quality parameters at various locations of the district.…”
Section: Fig1 Study Areamentioning
confidence: 99%
“…This study reveals that the aquifers of this region are subjected to continuous influence of seawater-groundwater mixing. According to various studies, over-exploitation and over-pumping is the primary cause of SWI in the coastal region of West Bengal and therefore various geophysical and geochemical investigations are carried out to identify the SWI [79][80][81][82]. In the coastline of Andhra Pradesh, rise in sea-level plays a significant role in enhancing the SWI with deteriorating the quality of groundwater and degrading the agricultural lands [83,84].…”
Section: Seawater Intrusion: Indian Scenariomentioning
confidence: 99%